Quality Management of Academic Supervision by Principals in Improving Elementary School Teachers' Performance: A Qualitative Study at SD IT Matahati and SD Al-Falah Boarding School, Bandung Regency - Syatiri Ahmad; Hanafiah Hanafiah; Endang Koswara; R. Supyan Sauri (Journal of Science and Education (JSE), 2026)
The gap that occurs in elementary schools is related to the principal's academic supervision between performance demands that are still suboptimal. However, the function of the principal's academic supervision in improving the performance of elementary school teachers remains suboptimal. This study aimed to determine and analyze the planning, implementation, evaluation, follow-up, constraints, and solutions for improving the performance of elementary school teachers. The approach used was a descriptive qualitative method with data collection techniques through observation, interviews, documentation studies, and triangulation. The results of this study show that (1) the principal's academic supervision planning is based on objectives, making supervision schedules, compiling supervision instruments, and analyzing schoolwork programs; (2) implementation through classroom visits, classroom observations, and providing learning tools; and (3) evaluation consisting of mastery of material and communication with students. (3) Evaluation, consisting of mastery of material, communication with students, types and evaluation techniques; (4) follow-up, enrichment, improvement, coaching, reflection and reporting; (5) obstacles, namely the lack of linear education personnel, inadequate facilities, and late payment of tuition fees for some students; (6) solutions for human resources, namely the procurement of teachers who are in accordance with the needs of elementary schools, namely PGSD graduates and training such as in-house training (IHT), seminars, and workshops in developing teacher soft skills. Facilities and infrastructure solutions, namely procurement of new classes and adequate fields for teaching and learning activities. The financing solution is the school's cooperation with student guardians in terms of tuition payments and home visits when payments are due with a prior notification letter from the school. billing either in the form of a certificate, informing via wa or telephone, and finally, through home visits to student guardians for those who are late in paying.